Odnos študentov do HIV pozitivnih - Dobnik, Mojca (Obzornik zdravstvene nege, 2002)
The article presents the research study performed among the students of the Maribor University in 2001 and presents the knowledge of the researched group,their attitude towards the HIV positive and their own knowledge about the disease. In this age group, health education performed by nurses proved tobe very efficient.
Keywords: Adult; ankete; Attitude; HIV; Hiv infections; HIV infekcije; Hiv seropositivity; HIV seropozitivnost; infekcije; Odnos; Odrasli; Prevention and control; Questionnaires; student; Students; Študenti